Effect of use of natural biologically active substances on shelf life of pomegranate fruits - Ozodov Nurbek Ismoil ugli; Ganiyeva Nozima Akmal qizi; Bahodirova Sevinchoy Anvar qizi; Nematov Nurillo Abdurakhim ugli (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
In this article, research on the effect of biologically active substances on the shelf life of pomegranate fruits and scientific data on various diseases, storage temperature, and relative humidity changes of pomegranate fruits during storage are presented